2017
DOI: 10.1016/j.dib.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Data for Korean college students׳ anxious and avoidant attachment, self-compassion, anxiety and depression

Abstract: The data presented in this article are from 473 Korean college students׳ responses to an online survey consisting of measures of anxious and avoidant attachment (the Experiences in Close Relationships-Revised Scale: ECR-R), self-compassion (Neff׳s Self-Compassion Scale: SCS), depression (the Center for Epidemiological Studies-Depression Scale: CES-D) and anxiety (the State-Trait Anxiety Inventory-the Trait Anxiety Scale: STAT-T). Each variable was measured by a Korean version of the instrument. Participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
3
2
0
Order By: Relevance
“…Regarding the criterion validity, the SCS-SF revealed good convergent and discriminative validity when the correlations with psychopathological indicators (i.e., DASS-21 scores) and social desirability, respectively, are analyzed. Correlations with psychopathological indicators showed very few differences between the long and reduced versions of the scale and similar to the ones found by national and international studies (Joeng et al, 2017;López, et al, 2018;Raes, 2010;Souza et al, 2020). The low correlation between the SCS-SF and social desirability, on the other hand, demonstrates that respondents are answering with honesty, and not according to what is socially desirable (Costa & Hauck Filho, 2017;Kwak et al, 2019) -although the internal consistency of the measure of social desirability was below expectations in the current study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding the criterion validity, the SCS-SF revealed good convergent and discriminative validity when the correlations with psychopathological indicators (i.e., DASS-21 scores) and social desirability, respectively, are analyzed. Correlations with psychopathological indicators showed very few differences between the long and reduced versions of the scale and similar to the ones found by national and international studies (Joeng et al, 2017;López, et al, 2018;Raes, 2010;Souza et al, 2020). The low correlation between the SCS-SF and social desirability, on the other hand, demonstrates that respondents are answering with honesty, and not according to what is socially desirable (Costa & Hauck Filho, 2017;Kwak et al, 2019) -although the internal consistency of the measure of social desirability was below expectations in the current study.…”
Section: Discussionsupporting
confidence: 87%
“…According to a Brazilian research conducted by Souza et al (2020), 298 adults responded to the SCS and the Depression, Anxiety and Stress Scale -Short Form (DASS-21) and the results showed a significant negative correlation between SC scores and DASS-21 global score (𝑟 = −.59), as well as with its subscales of depression (𝑟 = −.61), anxiety (𝑟 = −.44) and stress (𝑟 = −.49). These findings are similar to the ones described by Joeng et al (2017), López, Sanderman and Schroevers (2018) and Raes (2010), highlighting and presenting scientific evidence for the importance of SC and its assessment to assist mental health promotion interventions.…”
supporting
confidence: 86%
“…The SOCS-S total score and the CEAS-SC were significantly correlated in the predicted direction with all other measures. These findings are consistent with existing literature supporting the association of self-compassion with higher levels of mindfulness and well-being, and lower levels of psychological distress and insecure attachment [17,18,24,[116][117][118][119].…”
Section: Convergent Validitysupporting
confidence: 92%
“…In contrast, other studies have reported a more moderate correlation between attachment anxiety and generalized anxiety (e.g., r ≤ .24; Kidd et al, 2016; Meredith et al, 2016; Ng & Hou, 2017; Patel, 2008). Similarly, one large-scale study found a very large correlation between attachment avoidance and depression (e.g., r ≥ .47; Gallagher et al, 2017; Joeng et al, 2017; Pandeya, 2017), whereas other studies have reported a moderate correlation between these variables (e.g., r ≤ .20; Bekker & Croon, 2010; Gnilka et al, 2013; Necef, 2014; Ng & Hou, 2017; Rholes et al, 2011).…”
Section: Adult Attachmentmentioning
confidence: 96%